Regulatory mechanism of daily sleep by miR‐276a. Issue 1 (18th December 2020) - Zhang, Ruifeng; Zhao, Xianguo; Du, Juan; Wei, Liya; Zhao, Zhangwu
Abstract: MiRNAs have attracted more attention in recent years as regulators of sleep and circadian rhythms after their roles in circadian rhythm and sleep were discovered. In this study, we explored the roles of the miR‐276a on daily sleep in Drosophila melanogaster, and found a regulatory cycle for the miR‐276a pathway, in which miR‐276a, regulated by the core CLOCK/CYCLE (CLK/CYC) transcription factor upstream, regulates sleep via suppressing targets TIM and NPFR1. (a) Loss of miR‐276a function makes the flies sleep more during both daytime and nighttime, while flies with gain of miR‐276a function sleep less; (b) MiR‐276a is widely expressed in the mushroom body (MB), the pars intercerebralis (PI) and some clock neurons lateral dorsal neurons (LNds), in which tim neurons is important for sleep regulation; (c) MiR‐276a promoter is identified to locate in the 8th fragment (aFrag8) of the pre‐miR‐276a, and this fragment is directly activated and regulated by CLK/CYC; (4) MiR‐276a is rhythmically oscillating in heads of the wild‐type w 1118, but this oscillation disappears in the loss of function mutant clk jrk ; (5) The neuropeptide F receptor 1 ( npfr1) was found to be a downstream target of miR‐276a . These results clarify that the miR‐276a is a very important factor for sleep regulation.